2014
DOI: 10.1111/cid.12234
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Histomorphometric Evaluation of Fresh Frozen Bone Allograft in Sinus Lift Surgery

Abstract: FFB allograft was shown to be a feasible substitute for autogenous bone graft in sinus lift surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(47 reference statements)
1
3
0
Order By: Relevance
“…Besides, a study revealed that osteocyte lacunar volumes were unaffected by both age and sex [59]. In the current study the bone integrity index calculated as the ratio between osteocyte cells and osteocyte lacunae ( Figure 1D and Figure 3), as described by de Castilho [39], established osteocyte survival inside lacunae in exhumed bones. These findings are important because are related to bones inhumed between eight and twelve years in tropical soil.…”
Section: Fsi _2018supporting
confidence: 73%
See 1 more Smart Citation
“…Besides, a study revealed that osteocyte lacunar volumes were unaffected by both age and sex [59]. In the current study the bone integrity index calculated as the ratio between osteocyte cells and osteocyte lacunae ( Figure 1D and Figure 3), as described by de Castilho [39], established osteocyte survival inside lacunae in exhumed bones. These findings are important because are related to bones inhumed between eight and twelve years in tropical soil.…”
Section: Fsi _2018supporting
confidence: 73%
“…Cell index was calculated as the ratio between total mean of osteocytes and osteocyte lacunae [39] in preserved areas, for each case. After scanning the HE-stained sections at a low magnification (100x), the areas of highest concentration of osteocytes in the bone were located and chosen as hot spots.…”
Section: Fsi _2018mentioning
confidence: 99%
“…Reasons for excluding studies after full-text assessment were as follows: less than five patients included [46], less than five sinus augmentation procedures in each group [47], controlled clinical trials without randomization [48][49][50][51][52], MSFA in conjunction with additional augmentation procedures [53], alveolar ridge augmentation not involving MSFA [54], autogenous bone block graft was used as grafting material [55], histomorphometric outcome was not expressed in percentage [56], and MSFA was conducted with the use of space-maintaining mesh [57].…”
Section: Exclusion Of Studiesmentioning
confidence: 99%
“…Allogeneic fresh frozen bone (FFB) has been widely used for years in orthopedic reconstructive surgery and reported to have different successful applications in the oral and maxillofacial district, including ridge augmentation [29][30][31][32], reconstruction of large post-traumatic or post-oncologic defects [33][34][35], and sinus floor elevation [36][37][38][39][40]. FFB is osteoconductive and weakly osteoinductive, and its main advantages compared to the autogenous bone are its unlimited availability coupled with the lower morbidity for the patient, with no necessity of second surgical site to harvest the graft.…”
Section: Discussionmentioning
confidence: 99%